Hypertensive disorders of pregnancy increase the risk of developing neovascular age-related macular degeneration in later life. (3rd July 2019) - Curtin, Karen; Theilen, Lauren H.; Fraser, Alison; Smith, Ken R.; Varner, Michael W.; Hageman, Gregory S.
ABSTRACT: Background : Hypertensive disorders of pregnancy (HDP) and short-term adverse outcomes have long been recognized; however, survivors remain at risk of long-term complications. We investigated whether HDP is associated with the development of choroidal neovascular age-related macular degeneration (CNV AMD). Methods : We identified 31, 454 women who experienced HDP based on Utah birth certificates and 62, 908 unexposed women matched 2:1 to the exposed. Risk of CNV AMD was estimated using Cox models. Findings : Women with HDP exhibited an 80% higher risk for early CNV AMD (age < 70 y; 95%CI 1.23–2.58). Conclusion : Our findings may have implications forearlier CNV AMD screening and detection.